MANAJEMEN PESANTREN RAMAH ANAK (STUDI KUALITATIF TENTANG PERAN PENGASUHAN DAN KEMUSYRIFAN DI PONDOK PESANTREN AL-BAHJAH CIREBON) - Nur Sobarie; Fatimah Az Zahro (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2025)
Islamic boarding schools (pesantren) are increasingly required to provide a safe, humanistic, and violence-free learning environment in line with the paradigm of Child-Friendly Pesantren (CFP). This study analyzes how caregiving management and the musyrif system at Pondok Pesantren Al-Bahjah Cirebon are implemented to realize a CFP model grounded in the values of rahmah (compassion) and ta’dib (formation of proper conduct). Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews, and document analysis, and examined using Miles, Huberman, and Saldaña’s interactive model. The findings show that all managerial functions—planning, organizing, directing, and controlling—are driven by compassion and moral cultivation, leading the caregiving process to prioritize moral awareness over punishment. Value-based planning is translated into a tiered musyrif structure; caregiving implementation manifests through role modeling, dialogic guidance, and psychological support via SiPePsi; while reflective supervision through muhasabah and hisbah protects students’ dignity and emotional well-being. The integration of values throughout the management cycle produces a rahmah–ta’dib-based CFP model that reinforces spiritual character and psychological resilience. The study enriches the theoretical discourse on value-based Islamic educational management and offers practical directions for strengthening musyrif training. Comparative and longitudinal studies are recommended to examine the model’s consistency across pesantren with different characteristics.